Crystals of pyrrolidine compounds

By trying more than 1,000 conditions, crystals of pyrrolidinium A and phosphoric acid with excellent quality were successfully obtained, and the deliquesity and chemical stability of pyrrolidinium A in the prior art were solved, and the effect suitable as a pharmaceutical original drug was achieved.

CN113226314BActive Publication Date: 2025-03-18TANABE PHARMA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201980086473.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-27
Publication Date
2025-03-18
Estimated Expiration
2039-12-27

AI Technical Summary

Technical Problem

In the prior art, the hydrochloride salt of pyrrolidin compound A is not easy to crystallize, has deliquesity, and is not suitable as a primary drug for pharmaceutical products.

Method used

Through attempting crystallization through more than 1,000 conditions, it was found that crystals containing equimolar amounts of pyrrolidine compound A and phosphoric acid have excellent purity, thermal stability, hygroscopicity, deliquesity and chemical stability, and are suitable as original medicines for pharmaceutical products.

Benefits of technology

The crystals of pyrrolidinium compound A with the quality of the pharmaceutical raw drug were obtained, which solved the problems of deliquesity and chemical stability, and ensured the safety and stability of the drug.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003376155700000051
    Figure GDA0003376155700000051
  • Figure GDA0003376155700000101
    Figure GDA0003376155700000101
  • Figure GDA0003376155700000121
    Figure GDA0003376155700000121
Patent Text Reader

Abstract

The present invention provides a crystal of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidine-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid having a certain quality that can be used as a pharmaceutical original drug. Specifically, the present invention provides a crystal containing 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidine-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid and phosphoric acid in equimolar amounts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a crystal containing 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid (hereinafter, sometimes referred to as "pyrrolidine compound A" or "compound A") and phosphoric acid. More specifically, it relates to a crystal containing equimolar amounts of pyrrolidine compound A and phosphoric acid (hereinafter, sometimes referred to as "the present invention crystal") having excellent properties as a pharmaceutical raw material, and a pharmaceutical composition containing the same as an active ingredient. Background Art

[0002] International Publication No. WO2015 / 182723 (hereinafter referred to as Patent Document 1) discloses that pyrrolidine compounds or pharmacologically acceptable salts thereof having melanocortin receptor 1 (MC1R) agonist activity (agonist activity), and these compounds and pharmaceutical compositions containing these compounds as active ingredients are useful in the treatment or prevention of various diseases that are expected to improve symptoms by MC1R activation, and Example 19 describes the hydrochloride of pyrrolidine compound A. However, Patent Document 1 does not describe or teach crystals of pyrrolidine compound A.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. WO2015 / 182723 Pamphlet Summary of the invention

[0006] Problems to be solved by the invention

[0007] An object of the present invention is to provide a crystal of a pyrrolidine compound A having a certain quality that can be used as a raw material of a pharmaceutical.

[0008] Means for solving problems

[0009] It was found that the hydrochloride of pyrrolidine compound A does not crystallize, has deliquescent properties, and is not suitable as a pharmaceutical raw material. Therefore, for pyrrolidine compound A, in order to obtain crystals with a certain quality that can be used as a pharmaceutical raw material, the inventors of the present application tried crystallization under more than 1,000 conditions. As a result, it was found that from the perspective of purity, thermal stability, hygroscopicity, deliquescent properties, chemical stability and safety, crystals containing equimolar amounts of pyrrolidine compound A and phosphoric acid are crystals with a certain quality that can be used as a pharmaceutical raw material, thereby completing the present invention.

[0010] In addition, it was found that the crystals containing equimolar amounts of pyrrolidine compound A and phosphoric acid were difficult to crystallize. Therefore, the inventors of the present application studied the conditions for obtaining crystals with sufficient purity in a short time with good reproducibility. It was confirmed that according to the composition of the crystallization temperature and the crystallization solvent, there were problems such as increased impurities, delayed precipitation, and deterioration of stirring fluidity and filterability due to the miniaturization of the crystals. In order to solve these problems, in addition to conducting in-depth research on the types or amounts, ratios, etc. of reagents and solvents used in crystallization, the inventors of the present application also conducted in-depth research on the steps of crystallization, and found a method for efficiently obtaining crystals with few impurities, good operability of filtration, etc., and having a quality suitable for pharmaceutical original drugs.

[0011] The present invention relates to the following contents. [1]

[0013] Crystals comprising equimolar amounts of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid and phosphoric acid. [2]

[0015] The crystal as described in [1], which is formed from equimolar amounts of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid and phosphoric acid. [3]

[0017] The crystal as described in any one of [1] or [2], which is a co-crystal of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid and phosphoric acid. [4]

[0019] The crystal according to any one of [1] to [3], wherein in a powder X-ray diffraction spectrum, peaks are shown at diffraction angles represented by 2θ of 5.7°, 11.5°, 13.9°, 19.0° and 21.9° (each ±0.2°). [5]

[0021] The crystal according to any one of [1] to [4], which has an endothermic peak at 230°C to 240°C in differential scanning calorimetry analysis. [6]

[0023] The crystals as described in any one of [1] to [5] are obtained by adding seed crystals to a mixture of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid, phosphoric acid and a good solvent. [7]

[0025] The crystals as described in any one of [1] to [6] are obtained by adding a poor solvent to a mixture of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid, phosphoric acid and a good solvent, adding seed crystals, and then further adding a poor solvent. [8]

[0027] A melanocortin receptor 1 agonist comprising the crystal according to any one of [1] to [7] as an active ingredient. [9]

[0029] A pharmaceutical composition comprising the crystal according to any one of [1] to [7] and a pharmaceutically acceptable additive.

[10]

[0031] The pharmaceutical composition according to [9] is used for preventing or treating a disease whose symptoms are expected to be improved by activating melanocortin receptor 1.

[11]

[0033] A pharmaceutical composition as described in

[10] , wherein the disease is one or more diseases selected from rheumatoid arthritis, gouty arthritis, osteoarthritis, inflammatory bowel disease, systemic sclerosis, psoriasis, fibrosis, protoporphyria, systemic lupus erythematosus, melanoma, skin cancer, vitiligo, alopecia, pain, ischemia / reperfusion injury, inflammatory diseases of the brain, hepatitis, sepsis / septic shock, nephritis, transplantation, exacerbation of HIV disease, vasculitis, uveitis, retinitis pigmentosa, age-related macular degeneration, microbial infection, celiac disease, nephrotic syndrome and melanoma infiltration.

[12]

[0035] A method for preventing or treating a disease whose symptoms are expected to be improved by activation of melanocortin receptor 1, comprising administering an effective amount of the crystal according to any one of [1] to [7] to a patient.

[13]

[0037] Use of the crystal according to any one of [1] to [7] for producing a medicament for preventing or treating a disease whose symptoms are expected to be improved by activation of melanocortin receptor 1.

[14]

[0039] The crystal according to any one of [1] to [7], which is used for preventing or treating a disease whose symptoms are expected to be improved by activation of melanocortin receptor 1.

[0040] The present invention also relates to the following contents.

[15]

[0042] A method for producing a crystal according to any one of [1] to [5], comprising the step of adding seed crystals to a mixture of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid, phosphoric acid and a good solvent.

[16]

[0044] The production method as described in

[15] comprises the following steps: adding a poor solvent to a mixture of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid, phosphoric acid and a good solvent, adding seed crystals, and then further adding a poor solvent.

[0045] Effects of the Invention

[0046] The crystals containing equimolar amounts of pyrrolidine compound A and phosphoric acid are as follows: no solvent used to obtain the crystals remains; excellent thermal stability; stable with little weight change relative to humidity; non-deliquescent; excellent chemical stability; and do not contain compounds that may have adverse effects on organisms from the perspective of safety. Since the crystals can be obtained with good reproducibility using an industrially suitable method, they are useful as pharmaceutical raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] [ Figure 1 ] Figure 1 This is a diagram showing the results of powder X-ray diffraction measurement of the crystal of the present invention.

[0048] [ Figure 2 ] Figure 2 This is a graph showing the results of differential scanning calorimetry of the crystal of the present invention.

[0049] [ Figure 3 ] Figure 3This is a diagram showing an ORTEP diagram based on single crystal X-ray diffraction measurement of molecules in the crystal of the present invention.

[0050] [ Figure 4 ] Figure 4 It is a diagram showing a stacking diagram (a-axis projection diagram) based on single crystal X-ray diffraction measurement of molecules in the crystal of the present invention.

[0051] [ Figure 5-1 ] Figure 5-1 Graph showing the particle size distribution of the crystal obtained under condition 1 in Experimental Example 7.

[0052] [ Figure 5-2 ] Figure 5-2 Graph showing the particle size distribution of the crystal obtained under condition 3 in Experimental Example 7. DETAILED DESCRIPTION

[0053] The present invention relates to a crystal containing equimolar amounts of a pyrrolidine compound A represented by the following formula and phosphoric acid, and a pharmaceutical composition containing the crystal as an active ingredient.

[0054] [Chemical formula 1]

[0055]

[0056] The pyrrolidine compound A and / or phosphoric acid in the crystal of the present invention include isotopes (e.g., 3 H. 13 C. 14 C. 15 N. 18 F. 32 P, etc.) and deuterated transformants.

[0057] In the present invention, with respect to the crystals containing equimolar amounts of pyrrolidine compound A and phosphoric acid, other molecules such as the solvent used to obtain the crystals do not remain, and the pyrrolidine compound A and phosphoric acid constitute the crystals in a molar ratio of 1:1, that is, the crystals contain 1 molar equivalent of phosphoric acid relative to the pyrrolidine compound A.

[0058] As a preferred embodiment of the crystal of the present invention, there can be mentioned a co-crystal in which the pyrrolidine compound A and phosphoric acid do not form a salt, but the pyrrolidine compound A and phosphoric acid are bonded by non-ionic bonds and / or non-covalent bonds at a molar ratio of 1:1. In one embodiment, the crystal of the present invention exhibits Figure 1The powder X-ray diffraction pattern shown in FIG. 1 has characteristic peaks at diffraction angles represented by 2θ at 5.7°, 11.5°, 13.9°, 19.0° and / or 21.9° (±0.2°, respectively). More specifically, the powder X-ray diffraction pattern shown in FIG. 1 has peaks at diffraction angles represented by 2θ at 5.7°, 11.5°, 13.9°, 17.4°, 19.0°, 20.4° and / or 21.9° (±0.2°, respectively). More specifically, the diffraction angle represented by 2θ has peaks at 5.7°, 7.4°, 11.5°, 12.3°, 13.9°, 17.4°, 19.0°, 20.4° and / or 21.9° (±0.2°, respectively). More specifically, the diffraction angle represented by 2θ has peaks as shown in Table 2 (hereinafter, crystals having these peaks are sometimes referred to as B-type crystals or phosphate B-type crystals). In another embodiment, the B-type crystals show Figure 2 The differential scanning calorimetry (hereinafter, sometimes referred to as DSC) curve shown has an endothermic peak at 230°C to 240°C.

[0059] The crystal of the present invention is a crystal in which the residual solvent is below the reference value specified by the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (hereinafter referred to as ICH), which has an advantageous effect in this respect. In addition, as other advantages, it can be cited that the crystal is a crystal in which the organic impurities, inorganic impurities, residual metals, residual solvents, genotoxic impurities, etc. are below the reference values ​​specified in the guidelines of ICH.

[0060] In addition, as the crystal of the present invention, it is preferred to manufacture it as a crystal with a mode particle size of 7 μm or more for non-agglomerated crystals, and it can be mentioned that it is manufactured to be more preferably 7 to 15 μm, and particularly preferably 8 to 12 μm. The mode particle size refers to the particle size when the volume % of the particle size distribution takes a maximum value. In the method for manufacturing the crystal of the present invention, by making at least 70% or more, preferably 80% or more, and more preferably 90% or more of all the crystals have such a mode particle size, the operability such as the ease of crystal filtration is improved.

[0061] The crystal of the present invention can be obtained, for example, by reacting 1 to 10 mol, preferably 1 to 5 mol, of phosphoric acid with 1 mol of pyrrolidine compound A which can be produced by the method described in Example 19 of Patent Document 1. Alternatively, the crystal can be produced by the method described in the examples below.

[0062] The solvent for obtaining the crystal of the present invention can be appropriately selected, for example, a good solvent or a poor solvent can be used alone or in combination as appropriate. As a good solvent, as long as it is a solvent with high solubility of pyrrolidine compound A, it is not limited, for example, ketones (for example, acetone, 2-butanone, etc.), esters (for example, ethyl acetate, methyl acetate, etc.), alcohols (for example, methanol, ethanol, isopropanol, etc.), and mixtures of these solvents can be cited. As a poor solvent, as long as it is a solvent with low solubility of pyrrolidine compound A, it is not limited, for example, water, alkanes (for example, hexane, heptane, etc.), aromatic hydrocarbons (for example, benzene, toluene, etc.), ethers (for example, ether, dimethyl ether, diisopropyl ether, etc.), and mixtures of these solvents can be cited.

[0063] As one embodiment of the method for obtaining the crystal of the present invention, the following method can be mentioned: phosphoric acid is added to a mixture of pyrrolidine compound A and a good solvent, seed crystals are added to the obtained mixture, and the mixture is filtered. Preferably, the following method can be mentioned: pyrrolidine compound A is dissolved in a good solvent, phosphoric acid is added, seed crystals are added to the obtained mixture, and the mixture is filtered. More preferably, the following method can be mentioned: pyrrolidine compound A is dissolved in ethyl acetate or ethanol, phosphoric acid is added, seed crystals are added to the obtained mixture, and the mixture is filtered.

[0064] In addition, as another mode, the following method can be cited: phosphoric acid is added to a mixture of pyrrolidine compound A and a good solvent, a poor solvent is added to the obtained mixture, and the mixture is filtered. Preferably, the following method can be cited: pyrrolidine compound A is dissolved in a good solvent, phosphoric acid is added, a poor solvent is added to the obtained mixture, seed crystals are added, and the mixture is filtered. More preferably, the following method can be cited: pyrrolidine compound A is dissolved in a good solvent, phosphoric acid is added, a poor solvent is added to the obtained mixture, seed crystals are added, and the poor solvent is added, and the mixture is filtered. Further preferably, the following method can be cited: pyrrolidine compound A is dissolved in a good solvent, phosphoric acid is added, water is added to the obtained mixture, seed crystals are added, and water is added, and the mixture is filtered.

[0065] As suitable combinations and ratios when a good solvent and a poor solvent are used in combination, for example, ethanol: toluene = 1: 9, ethanol: diisopropyl ether = 3: 7, acetone: toluene = 3: 7, etc. can be cited. As examples of suitable good solvents when a good solvent is used in combination with water, ethyl acetate, ethanol, etc. can be cited. When a good solvent and a poor solvent (specifically, water) are used in combination, and water is added twice before and after the addition of seed crystals, it is preferred that the amount of water added before the addition of seed crystals (the first addition of water) is 3 times the weight of the pyrrolidine compound A by volume ratio, and the amount of water added after the addition of seed crystals (the second addition of water) is 4.5 times the weight of the pyrrolidine compound A by volume ratio. As another embodiment, the following method can be cited: the amount of water added is 5 to 10 times the weight of the pyrrolidine compound A by volume ratio, and is added in batches before and after the addition of seed crystals. More preferably, the amount of water is 6 to 9 times, more preferably 7.5 times, by volume relative to the weight of the pyrrolidine compound A. In addition, as another embodiment, the following example can be cited: the amount of water added for the first time and the amount of water added for the second time are 1:1 to 1:2 by volume, preferably 2:3. As another embodiment, the following example can be cited: water is added before adding the seed crystals to the extent that 70% or more, preferably 80% or more of the crystals are precipitated after the addition of the seed crystals and before the addition of water. In addition, the following example can be cited: the temperature when adding the seed crystals is set to 28 to 32°C, preferably 30°C. This temperature is also preferably selected as the temperature at which 70% or more, preferably 80% or more of the crystals are precipitated after the addition of the seed crystals and before the addition of water.

[0066] The seed crystal of the crystal of the present invention can be obtained by the method described in Example 3, Experimental Example 2 or Experimental Example 3 described later. In addition, the crystals obtained by these methods can also be used as the seed crystal of the crystal of the present invention, and the seed crystal can be obtained by, for example, the method described in Example 1 or 2 or a method based on the method described in Example 1 or 2.

[0067] The crystal of the present invention has human MC1R agonist activity, and thus can be used as an active ingredient of a melanocortin receptor 1 agonist. In addition, the crystal of the present invention and a pharmaceutical composition containing the crystal as an active ingredient are useful in treating or preventing various diseases that are expected to improve symptoms by MC1R activation. Such diseases include, for example, rheumatoid arthritis, gouty arthritis, osteoarthritis, inflammatory bowel disease, systemic sclerosis, psoriasis, fibrosis, protoporphyria (e.g., erythropoietic protoporphyria, etc.), systemic lupus erythematosus, melanoma, skin cancer, vitiligo, alopecia, pain, ischemia / reperfusion injury, inflammatory diseases of the brain, hepatitis, sepsis / septic shock, nephritis, transplantation, exacerbation of HIV disease, vasculitis, uveitis, retinitis pigmentosa, age-related macular degeneration, microbial infection, coeliac disease, nephrotic syndrome, and one or more diseases of melanoma infiltration. In particular, it is useful for treating or preventing one or more diseases selected from systemic scleroderma, psoriasis, protoporphyria, melanoma, skin cancer, vitiligo, hair loss, retinitis pigmentosa, age-related macular degeneration, and nephrotic syndrome. In particular, it is useful for treating or preventing one or more diseases selected from systemic scleroderma, protoporphyria, melanoma, vitiligo, retinitis pigmentosa, age-related macular degeneration, and nephrotic syndrome.

[0068] The pharmaceutical composition containing the crystal of the present invention as an active ingredient can be obtained by mixing the crystal of the present invention with pharmaceutically acceptable additives such as excipients, disintegrants, binders, lubricants, coating agents, pigments, diluents, bases and isotonic agents.

[0069] The crystal of the present invention and the pharmaceutical composition containing the crystal as an active ingredient can be prepared into a suitable administration form (e.g., powder, injection, tablet, capsule, topical preparation, etc.), and then administered to a patient by a suitable administration method corresponding to the administration form (e.g., intravenous administration, oral administration, and transdermal administration, etc.). The term "patient" in the present invention refers to an individual who is the object of prevention or treatment by the crystal of the present invention, preferably a mammal, and more preferably a human.

[0070] The dosage can be determined based on the patient's age, weight, general health, sex, diet, administration time, administration method, excretion rate, combination of drugs, and the degree of the patient's condition being treated at the time of administration, based on consideration of these factors or other factors. The crystal of the present invention and the pharmaceutical composition containing it as an active ingredient have low toxicity and can be used safely. The daily dosage (i.e., effective dosage) varies depending on the patient's condition, weight, administration route, etc. For example, in the case of parenteral administration, it is expected to be administered in an amount of about 0.0001 to 1000 mg / person / day, preferably about 0.001 to 1000 mg / person / day, and particularly preferably 0.01 to 500 mg / person / day. In addition, in the case of oral administration, it is expected to be administered in an amount of about 0.0001 to 1000 mg / person / day, preferably 0.01 to 500 mg / person / day.

[0071] In the present invention, the term "prevention" refers to the act of administering the crystal of the present invention or a pharmaceutical composition containing the crystal to an individual who has not developed a disease, illness, or symptom. In addition, the term "treatment" refers to the act of administering the crystal of the present invention or a pharmaceutical composition containing the crystal to an individual who has developed a disease, illness, or symptom. Therefore, the act of administering the crystal to an individual who has developed a disease, illness, or symptom in order to prevent the deterioration of symptoms, the onset of a disease, or the recurrence of a disease is a form of "treatment".

[0072] Example

[0073] The present invention will be described in detail below by way of examples and experimental examples, but the present invention is not limited thereto. It should be noted that "equivalent" means "molar equivalent".

[0074] Example 1 Synthesis of the Crystal of the Present Invention

[0075] [Chemical formula 2]

[0076]

[0077] Make compound 1 (26.18 g) was dissolved in dichloromethane (207 mL), and the compound 2 (4.4 mL) and acetic acid (3.56 mL), and stirred at room temperature for 30 minutes. Then, sodium triacetoxyborohydride (13.2 g) was further added, and stirred at room temperature for 1 hour. After adding saturated sodium bicarbonate aqueous solution and stirring, extraction was performed with dichloromethane. The obtained organic layer was washed with saturated saline solution, dried with magnesium sulfate, and concentrated under reduced pressure. The residue was purified by NH silica gel column chromatography (hexane: ethyl acetate = 75:25 ~ 55:45) and then silica gel column chromatography (chloroform: methanol = 100:0 ~ 95:5) to obtain the compound as a colorless powder.3 (24.25g)(MS(ESI): m / z 690[M+H] + ).

[0078] Make compound 3 (24.24 g) was dissolved in methanol (240 mL), and an aqueous sodium hydroxide solution (2 mol / L, 70.2 mL) was added thereto, and the mixture was stirred at room temperature for 19 hours. Then, an aqueous hydrochloric acid solution (2 mol / L, 74 mL) was further added, and the reaction solution was concentrated under reduced pressure. Water and ethyl acetate were added to the concentrated residue, and after stirring, the mixture was extracted with ethyl acetate. The obtained organic layer was washed with a phosphate buffer solution (0.1 mol / L, 300 mL) and brine, dried over magnesium sulfate, and concentrated under reduced pressure. After the residue was purified by silica gel column chromatography (chloroform: methanol = 100:0 to 90:10), it was dissolved in ethyl acetate, a phosphate buffer solution (0.1 mol / L, 200 mL) was added, the mixture was stirred at room temperature, and extracted with ethyl acetate. The organic layer was washed with water and saturated brine, dried over magnesium sulfate, and concentrated under reduced pressure to obtain the compound as a colorless powder. 4 (23.7g)(MS(ESI): m / z 676[M+H] + ).

[0079] Make compound 4 (135 mg) was dissolved in ethanol (0.7 mL), and a small amount of the crystals of the present invention was added as seed crystals. A phosphoric acid solution obtained by dissolving phosphoric acid (25 mg) in ethanol (0.5 mL) was added thereto, and ethanol (0.2 mL) was further added, and stirred at room temperature overnight. The precipitated crystals were filtered out, washed with ethyl acetate (0.6 mL), and dried under reduced pressure at 50 ° C for 4 hours to obtain 112.7 mg of the crystals of the present invention. The presence or absence of residual solvent was confirmed by 1H-NMR, and no residual solvent was observed. The results of the elemental analysis are shown in Table 1 below.

[0080] [Table 1]

[0081] Table 1 <Elemental analysis results>

[0082] C H N P Measured value 55.21 6.14 5.31 3.96 Theoretical value 55.49 6.29 5.39 3.97

[0083] (The theoretical value indicates the theoretical value when 0.3 equivalent of water is attached.)

[0084] <Powder X-ray Diffraction (hereinafter, sometimes referred to as XRPD) Measurement>

[0085] The measurement was performed under the following conditions using a powder X-ray diffraction measuring apparatus X'Pert Pro (manufactured by PANalytical B.V.).

[0086] X-ray generating device: X-ray tube (cathode: copper, tube voltage: 45kV, tube current: 40mA)

[0087] Incident optical system: focusing condenser

[0088] Light receiving optical system: High-speed semiconductor array detector (X-Celerator), extended light receiving side arm

[0089] Sample stage: HTS sample stage (vibrates with a width of 4 mm in the X-axis direction)

[0090] Cumulative number of times: 5 times (the incident angle was changed to -2, -1, 0, 1, and 2 degrees respectively)

[0091] Measuring range: 2θ = 3 to 40°

[0092] Scanning speed: 0.668451° / sec

[0093] Interval: 0.0167°

[0094] The results are shown in Figure 1 The peaks having relative peak intensities of 5 or more when the peak intensity at a diffraction angle of 5.7° represented by 2θ is set to 100 are shown in Table 2 below.

[0095] [Table 2]

[0096] Table 2

[0097]

[0098] <Differential Scanning Calorimetry (DSC) Measurement>

[0099] The measurement was performed under the following conditions using a differential scanning calorimeter X-DSC7000 (SII NanoTechnology Co., Ltd.).

[0100] Heating rate: 10℃ / min (25℃~300℃)

[0101] Atmosphere: Nitrogen 100mL / min

[0102] The results are shown in Figure 2 An endothermic peak was observed at about 230°C to 240°C.

[0103] <Single crystal X-ray diffraction measurement>

[0104] Add about half of the crystal of the present invention with a spatula (small) to 2 mL of ethanol, dissolve, and let stand at room temperature for 4 days to crystallize. Using the single crystal X-ray diffraction device R-AXIS RAPID / R (Rigaku) ​​(CuKα line), the lattice constant of the obtained crystal is determined and the diffraction peak intensity is measured at 23°C, and then the phase is determined by the direct method, and the structure is refined and analyzed by the full matrix least squares method. The obtained crystallographic data and crystal structure analysis results are shown in Table 3. It should be noted that the reliability factor (R value) is 3.06%, and various other parameters also show that the present crystal structure analysis is an analysis result with sufficiently high reliability.

[0105] [Table 3]

[0106] Table 3 Crystallographic data and crystal structure analysis results

[0107]

[0108] The ORTEP diagram of the molecule in the crystal of the present invention is shown in Figure 3 , the stacking diagram is shown in Figure 4 In the crystal, one molecule of the pyrrolidine compound A and one molecule of phosphoric acid are independently present in the asymmetric unit.

[0109] The absolute configuration of the crystal of the present invention was verified, and the Flack parameter was 0.02(3), thus confirming that the crystal of the present invention is Figure 3 The crystal shown has one molecule of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid and one molecule of phosphoric acid as constituent units.

[0110] The Regulatory Classification of Pharmaceutical Co-Crystals Guidance for International Use issued by the U.S. Food and Drug Administration (FDA) states that a co-crystal is a crystal containing two or more different molecules in the crystal lattice, and these molecules are bonded by non-ionic bonds and / or non-covalent bonds. The above-mentioned crystal structure analysis has confirmed that there is no covalent bond between pyrrolidine compound A and phosphoric acid, so whether an ionic interaction is found between pyrrolidine compound A and phosphoric acid is studied.

[0111] Since phosphoric acid is a Bronsted acid, when it is considered that ion interaction occurs with pyrrolidine compound A, pyrrolidine compound A must accept protons as a Bronsted base. In the case of pyrrolidine compound A, three nitrogens (N18, N19, and N20) may accept protons from phosphoric acid. Here, all hydrogen bonding sites in the crystal of the present invention are shown in Table 4.

[0112] [Table 4]

[0113] Table 4 Hydrogen bonding sites in the crystals of the present invention

[0114]

[0115] (1)N18

[0116] N18 is sp3 hybridized nitrogen, which has the highest basicity in pyrrolidine compound A and is likely to accept a proton from phosphoric acid. However, it is judged that N18 (more strictly speaking, the hydrogen atom bonded to N18) forms a hydrogen bond with the oxygen (O16) of the carboxylic acid of the adjacent pyrrolidine compound A (symmetry operators: -X+1 / 2+2, -Y+2, Z+1 / 2) and donates a proton. Therefore, N18 cannot accept a proton from phosphoric acid. At the same time, the interatomic distance between N18 and any oxygen of the adjacent phosphoric acid exceeds the sum of the van der Waals radius, so it is judged that phosphoric acid does not exist within the distance that can produce ionic interaction.

[0117] (2)N19

[0118] N19 is sp2 hybridized nitrogen, so it is weak in basicity and is not considered to be able to form a salt. At the same time, the interatomic distance between N19 and the nearest oxygen (O13) of phosphoric acid is the sum of the van der Waals radius, so it is judged that it is not within the distance where ionic interaction can occur.

[0119] (3)N20

[0120] N20 is also sp2 hybridized nitrogen, so it is weakly basic and is not considered to be able to form a salt. At the same time, the interatomic distance between N20 and any oxygen of the adjacent phosphoric acid also exceeds the sum of the van der Waals radius, so it is judged that there is no phosphoric acid within the distance that can produce ionic interaction.

[0121] According to the above results, the binding between nitrogen (N18, N19, N20) of pyrrolidine compound A and phosphoric acid in the crystal of the present invention is not based on ionic interaction, and pyrrolidine compound A and phosphoric acid do not form a salt, so the crystal of the present invention is judged to be a co-crystal. In this specification, the crystal obtained in this example is referred to as type B crystal.

[0122] Example 2 Synthesis of the Crystal of the Present Invention (2)

[0123] [Chemical formula 3]

[0124]

[0125] Compounds 3 1,2-ethanedisulfonic acid hydrate (38 mg) was added to a solution of (276 mg) in ethanol (1.4 mL), and the mixture was stirred at room temperature for 40 minutes. The crystals were filtered out and washed twice with ethanol (0.84 mL). The crystals were dried at 40°C or below to obtain the compound 5 (178 mg). 5 To a suspension of (37.1kg) of ethyl acetate (167.5kg), potassium carbonate (6.5kg) in water (148.3L) and water (36.8L) were added in sequence at room temperature, and the mixture was stirred at room temperature for 15 minutes. The aqueous layer was removed, the organic layer was washed twice with water (186L), ethyl acetate (67.2kg) was added, and the insoluble matter was filtered. After concentrating to 78L, ethanol (146.5kg) was added, and the mixture was concentrated to 78L. Ethanol (146.9kg) was added and concentrated to 56L. Diluted with ethanol (44kg), 24% sodium hydroxide aqueous solution (8.7kg) and water (30.1kg) were added in sequence at room temperature, and the mixture was stirred at 40°C for 5 hours to obtain the compound 4 At 30°C, add the compound 4 A solution of phosphoric acid (12.0 kg) in water (55.7 L) and water (55.7 L) were added to the solution in sequence. The crystal of the present invention was added as a seed crystal (928 g) and stirred for 14 hours. Water (167.0 L) was added, stirred for 4 hours, and then cooled to 25°C. The solid was filtered out and washed with water (182 L). The solid was dried at below 50°C to obtain the crystal of the present invention (35.2 kg). The crystal is a crystal with excellent operability such as filterability.

[0126] Experimental Example 1 Crystallization Study of Pyrrolidine Compound A

[0127] Using pyrrolidine compound A, the following studies were conducted: a crystallization study using 25 single solvents and 44 mixed solvents for long-term storage; a crystallization study using 96 mixed solvents (which are made by changing the mixing ratio of 2 poor solvents (Anti-solvent) and 12 good solvents (Good-solvent)) and stirring for 1 month; and a crystallization study using 26 added solvents for grinding (grinding). As a result, crystals were obtained through crystallization studies based on long-term storage and 1 month of stirring. The obtained crystals were subjected to powder X-ray diffraction measurement, and the results showed that the peaks in all crystals were consistent and were the same crystal form. The crystallization conditions were studied, and solvents remained in the crystals under all conditions that could obtain crystals. The process of drying the crystals was also studied, and the residual solvent could not be made below the residual solvent reference value established by ICH.

[0128] Therefore, although the pyrrolidine compound A as a free form is crystallized, the solvent used to obtain the crystal remains and the chemical stability is low, so it cannot be used as a pharmaceutical raw material.

[0129] Experimental Example 2 Crystallization Study of a Mixture Containing Pyrrolidine Compound A (1)

[0130] About 900 mg of pyrrolidine compound A was dissolved in 30 mL of tetrahydrofuran, and 100 μL (about 3 mg / vial) was dispensed into each vial of a 96-well plate. In addition, 21 acids including phosphoric acid, hydrochloric acid, L(-)-malic acid, L(+)-tartaric acid, maleic acid, sulfuric acid and malonic acid and 8 bases including sodium hydroxide and L-arginine (hereinafter sometimes referred to as counter compounds) were dissolved in 8 solvents described later, and 45 μL of the 0.1 mol / L solution thus obtained (for some acids, 90 μL of 0.05 mol / L solution) was dispensed into each vial. The solution was left open for 1 day and night to evaporate the solvent, and then dried under reduced pressure for 4 hours. After 250 μL of 8 solvents including ethyl acetate, acetone and toluene were dispensed into each vial, ultrasonically stirred for 5 minutes, sealed, and stirred at room temperature for 6 days. For the vials with precipitates, the precipitates were filtered out and XRPD was measured. The solvent was evaporated at room temperature for the vial without precipitate, and when solid was observed, it was filtered out and measured by XRPD. The XRPD measuring apparatus and measuring conditions were the same as those in Example 1.

[0131] From the combination of phosphoric acid and ethyl acetate, the combination of L (-)-malic acid and toluene, the combination of L (+)-tartaric acid and acetone, and the combination of maleic acid and toluene, phosphoric acid A-type crystals, L (-)-malic acid D-type crystals, L (+)-tartaric acid E-type crystals and maleic acid F-type crystals were obtained respectively. It should be noted that, in addition to these, there is also a crystal bottle that can confirm that only the paired compound is crystal, i.e., the crystal does not contain pyrrolidine compound A. On the other hand, using all 8 kinds of solvents, crystals cannot be obtained from the bottle added with hydrochloric acid. In addition, using all solvents, crystals cannot be obtained from the bottle added with sulfuric acid, malonic acid and L-arginine.

[0132] Experimental Example 3 Study on Crystallization of a Mixture Containing Pyrrolidine Compound A (2)

[0133] About 800 mg of pyrrolidine compound A was dissolved in 40 mL of tetrahydrofuran, and 100 μL (about 2 mg / vial) was dispensed into each vial of a 96-well plate. In addition, 22 acids including phosphoric acid, hydrochloric acid, L(-)-malic acid, L(+)-tartaric acid, maleic acid, sulfuric acid, and malonic acid, and 8 bases including sodium hydroxide and L-arginine (hereinafter sometimes referred to as paired compounds) were dissolved in 12 solvents described later, and 30 μL of the 0.1 mol / L solution thus obtained (for some acids, 60 μL of 0.05 mol / L solution) was dispensed into each vial. After the dispensing, nitrogen gas was sprayed to evaporate the solvent. 200 μL of 12 kinds of solvents including a mixed solvent of ethanol and toluene at a mixing ratio of 3:7 and 1:9, a mixed solvent of ethanol and diisopropyl ether at a mixing ratio of 3:7, a mixed solvent of acetone and toluene at a mixing ratio of 3:7 and 1:9, and a mixed solvent of ethyl acetate and heptane at a mixing ratio of 3:7 were dispensed into each vial, sealed, and stirred at room temperature for 3 days. For the vials with precipitates, the precipitates were filtered out and XRPD was measured. For the vials without precipitates, the solvent was evaporated at room temperature, and when solids were observed after about 1 month, the solids were collected and XRPD was measured. The XRPD measuring device and measuring conditions were the same as those in Example 1.

[0134] The vials containing the combinations of crystals obtained are shown in Table 5 below. In the table, "-" indicates that no crystal was obtained, and A, B, etc. indicate that crystal A and crystal B, etc. were obtained, respectively. That is, it is shown that the XRPD patterns of the F-type maleic acid crystals obtained this time are consistent with those of the F-type maleic acid crystals obtained in Experimental Example 2, and the B-type phosphoric acid crystals obtained this time are different crystals from the A-type phosphoric acid crystals obtained in Experimental Example 2. It should be noted that, similar to Experimental Example 2, in addition to the above, there are also vials in which only the crystals of the paired compounds could be confirmed. On the other hand, using all 12 solvents, no crystals could be obtained from the vials containing hydrochloric acid. In addition, regarding L(-)-malic acid and L(+)-tartaric acid, crystals were obtained in Experimental Example 2, but no crystals could be obtained this time using all 12 solvents.

[0135] [Table 5]

[0136] Table 5 Results of Crystallization Study (2) of Mixtures Containing Pyrrolidine Compound A

[0137]

[0138] Experimental Example 4 Crystallization Study (3) of Mixtures Containing Pyrrolidine Compound A

[0139] Among the crystals obtained in Experimental Examples 2 and 3, for crystals other than A-type phosphoric acid crystals and B-type phosphoric acid crystals, reproducibility was confirmed. As a result, L(-)-malic acid D-type crystals, L(+)-tartaric acid E-type crystals, sulfuric acid J-type crystals, and L-arginine K-type crystals could not be obtained again. On the other hand, crystals could be obtained again for the combination of maleic acid and malonic acid.

[0140] <L(-)-Malic Acid, L(+)-Tartaric Acid, and Sulfuric Acid>

[0141] Dissolve about 80 mg of pyrrolidine compound A in 4 mL of tetrahydrofuran, and dispense 100 μL (about 2 mg / vial) into each vial of a 96-well plate. In addition, dispense 30 μL each of 0.1 mol / L solutions obtained by dissolving L(-)-malic acid, L(+)-tartaric acid, and sulfuric acid in the solvents described below into each vial. After dispensing, evaporate the solvent by blowing nitrogen, and then dispense 200 μL of toluene into the vial containing L(-)-malic acid, 200 μL of acetone into the vial containing L(+)-tartaric acid, and a mixed solvent with a mixing ratio of 3:7 of ethyl acetate and heptane into the vial containing sulfuric acid, and seal. For each sample, 8 were prepared. Stir a total of 24 vials at room temperature for 7 days, but no precipitates were obtained in all vials.

[0142] <L-Arginine>

[0143] About 65 mg of pyrrolidine compound A was measured and dissolved in 0.3 mL of ethanol and 2.1 mL of toluene at room temperature. About 19 mg of L-arginine was measured, dissolved in 0.6 mL of ethanol and 0.6 mL of water, and added to the solution of the above-mentioned pyrrolidine compound A. Since it is a solution, the solvent is evaporated by blowing nitrogen, and a part of the sugar containing white powder is obtained. It is dissolved again in 0.3 mL of ethanol and 0.6 mL of diisopropyl ether is added dropwise. The L-arginine K-type crystals obtained in Experimental Example 3 are added as seed crystals, but they are dissolved, so 1.2 mL of toluene is added and stirred all night. Since it is a solution, the solvent is evaporated by blowing nitrogen, and the residue is subjected to XRPD measurement, and the result is amorphous. 0.6 mL of heptane is added thereto, and after stirring at room temperature overnight, microscopic observation is performed. No crystalline components are observed.

[0144] <Maleic Acid F-Type Crystal>

[0145] About 65 mg of pyrrolidine compound A was measured and dissolved in 0.5 mL of toluene at room temperature. A substance obtained by dissolving about 13 mg of maleic acid in 75 μL of ethanol and a small amount of maleic acid F-type crystals obtained before were added as seed crystals, and the reaction solution became a gel (agar-like) and could not be stirred. 1.0 mL of toluene was further added and rubbed vigorously with a spatula, resulting in a suspension. The filtered crystals were dried under reduced pressure at 40 ° C for 5 hours to obtain 57 mg of maleic acid F-type crystals. 1H-NMR confirmed that 0.1 equivalents of toluene remained in the obtained crystals.

[0146] <Malonate G-type crystal>

[0147] About 325 mg of pyrrolidine compound A was measured and dissolved in 1 mL of acetone at room temperature. 55 mg of malonic acid was measured and dissolved in 0.5 mL of acetone at room temperature, and added to the above-mentioned solution of pyrrolidine compound A. 6 mL of toluene was added dropwise to the solution. A small amount of malonic acid type I crystals described later was added as seed crystals, and stirred at room temperature for two nights. The entire amount was filtered and dried under reduced pressure at 40°C for 3.5 hours to obtain 317 mg of crystals. 1H-NMR confirmed that the obtained crystals contained 1 equivalent of toluene. In order to replace toluene with water, a dynamic vapor adsorption measurement (Dynamic Vapour Sorption: DVS) device was used and stored at 25°C and 70% RH for 72 hours, and amorphization was observed.

[0148] <Malonate H-type crystal>

[0149] About 65 mg of pyrrolidine compound A was measured and dissolved in 2 mL of a mixed solvent of ethyl acetate and heptane in a mixing ratio of 3:7 at room temperature. 11 mg of malonic acid was measured and dissolved in 0.3 mL of ethyl acetate at room temperature, and added to the above-mentioned solution of pyrrolidine compound A. Since a hard rubber-like substance was generated, 3 mL of ethyl acetate was added to make a suspension. After stirring at room temperature for 3 days, the solvent was evaporated by blowing nitrogen, 3 mL of ethyl acetate was added to the dried solid, stirred, and 1.2 mL of heptane was slowly added. When a small amount of malonic acid type G crystals obtained in Experimental Example 3 were added as seeds, precipitates were produced rapidly. After stirring at room temperature for two nights, the entire amount was filtered and dried under reduced pressure at 40°C for 3.5 hours to obtain 38 mg of crystals.

[0150] <Malonate I type crystal>

[0151] About 65 mg of pyrrolidine compound A was measured and dissolved in 2.3 mL of a mixed solvent of acetone and toluene at a mixing ratio of 1:9 at room temperature. 11 mg of malonic acid was measured and dissolved in 0.1 mL of acetone at room temperature, and added to the above solution of pyrrolidine compound A. After stirring at room temperature for 3 nights, the entire amount was filtered and dried under reduced pressure at 40°C for 2 hours to obtain 51 mg of crystals. 1H-NMR confirmed that the obtained crystals contained 1 equivalent of toluene. Since the crystals may be toluene compounds, in order to confirm whether solvent-free crystals can be obtained by further drying under reduced pressure, about 5 mg was dried under reduced pressure at 60°C for 4 hours. As a result, about 0.5 equivalents of toluene remained, confirming that the crystal form did not change.

[0152] Example 3 Synthesis of the Crystal of the Present Invention (3)

[0153] The pyrrolidine compound A and phosphoric acid in the amounts shown in Table 6 below were added to the solvent shown below, and stirred for the time shown below. The results are shown in Table 6 below. The XRPD measuring apparatus and measuring conditions were the same as those in Example 1. The XRPD results showed that A was the same crystal as the phosphoric acid type A crystal obtained in Experimental Example 2, and B was the same crystal as the phosphoric acid type B crystal obtained in Experimental Example 3. In addition, the phosphoric acid type B crystal was the same crystal as the crystal of the present invention obtained in Example 1.

[0154] [Table 6]

[0155] Table 6

[0156]

[0157] In the method (a), a mixture of type A crystals and type B crystals was obtained. According to the results of elemental analysis, the crystals contained 1.5 equivalents of phosphoric acid. In the method (f) using acetone / toluene solvent, new type C crystals were obtained. According to the results of elemental analysis, the type C crystals contained 2 equivalents of phosphoric acid. In addition, no matter which method was used, type A crystals could not be obtained alone.

[0158] In methods (a), (b), (c), (e) and (f), amorphous or sugar-like substances are generated immediately after the addition of phosphoric acid, but crystals can be obtained by stirring the amorphous substance at room temperature for 7 to 10 days or rubbing the sugar-like substance with a spatula for a long time. In addition, in method (d), a suspension of crystals is obtained one day after the start of crystallization, but it becomes a sugar-like substance after continuous stirring at room temperature for 4 days. Furthermore, the solvent is evaporated with nitrogen gas and stirred in ethanol at room temperature for one night, resulting in type B crystals.

[0159] Experimental Example 5 Synthesis of the hydrochloride salt of pyrrolidine compound A

[0160] [Chemical formula 4]

[0161]

[0162] Compounds 1 To a solution of (19.43 g) in chloroform (157 mL) was added the compound 2 (3.3 mL) and acetic acid (2.7 mL), stirred at room temperature for 30 minutes, then added sodium triacetoxyborohydride (10.0 g), and stirred at room temperature for 20 hours. After adding saturated sodium bicarbonate aqueous solution and stirring, it was extracted with chloroform. The obtained organic layer was washed with saturated sodium bicarbonate aqueous solution and saturated brine, dried with magnesium sulfate, and concentrated under reduced pressure. The residue was purified by NH silica gel column chromatography (hexane: ethyl acetate = 75:25 ~ 55:45), followed by silica gel column chromatography (chloroform: methanol = 100:0 ~ 95:5) and silica gel column chromatography (chloroform: methanol = 99:1 ~ 96:4) to obtain the compound as a colorless powder. 3 (21.92g)(MS(ESI): m / z 690[M+H] + ).

[0163] Compounds 3To a solution of (21.91 g) of methanol (200 mL) was added an aqueous sodium hydroxide solution (2 mol / L, 63.6 mL), and the mixture was stirred at room temperature for 3 hours. After adding an aqueous hydrochloric acid solution (2 mol / L, 63.6 mL), the reaction solution was concentrated under reduced pressure. Water and ethyl acetate were added to the concentrated residue, and after stirring, extraction was performed with ethyl acetate. The obtained organic layer was washed with a saturated saline solution, dried over magnesium sulfate, and concentrated under reduced pressure. The residue was purified by silica gel column chromatography (chloroform: methanol = 98:2 to 90:10), and then dissolved in ethyl acetate, a phosphate buffer solution (0.1 mol / L, 300 mL) was added, and the mixture was stirred at room temperature for 3 hours. After extraction with ethyl acetate, the organic layer was washed with a saturated saline solution, dried over magnesium sulfate, and concentrated under reduced pressure to obtain the compound as a colorless powder. 4 (17.40g)(MS(ESI): m / z 676[M+H] + ).

[0164] Compounds 4 To a solution of 17.40 g of ethyl acetate (250 mL) was added a hydrochloric acid-ethyl acetate solution (4 mol / L, 31.8 mL), and the mixture was stirred at room temperature for 30 minutes. The solvent was distilled off under reduced pressure, ether was added, the mixture was stirred, filtered, and dried under reduced pressure to obtain the compound as a colorless powder. 4 Hydrochloride (17.43 g) (MS (ESI): m / z 676 [M+H] + ).

[0165] Experimental Example 6 Comparison of amorphous hydrochloride of pyrrolidine compound A, amorphous pyrrolidine compound A, crystals of pyrrolidine compound A, and crystals of a mixture containing pyrrolidine compound A for which reproducibility has been confirmed

[0166] Since the hydrochloride of pyrrolidine compound A described in Example 19 of Patent Document 1 is amorphous, and no crystals of the hydrochloride of pyrrolidine compound A were obtained in subsequent studies (see Experimental Examples 2 and 3 above), the amorphous hydrochloride of pyrrolidine compound A was used for comparative tests. In addition, in the comparative test results shown below, the hydrochloride is the hydrochloride of pyrrolidine compound A, and the results of the compound obtained by the method described in Experimental Example 5 are shown.

[0167] In the comparative test results shown below, the amorphous free form is the amorphous free form of the pyrrolidine compound A, which shows that the compound obtained by the method described in Example 1 4 result.

[0168] In the comparative test results shown below, the free body crystals are crystals of the free body of pyrrolidine compound A. Experimental Example 1 shows that, for this crystal, it is impossible to make the residual solvent in the crystal below the reference value specified by ICH, and it has been confirmed that this crystal is not suitable as a crystal for a pharmaceutical raw material.

[0169] In the comparative test results shown below, for phosphate type A + type B crystals, the results of the crystals obtained by the (a) method described in Example 3 are shown, for phosphate type B crystals, the results of the crystals of the present invention obtained by the method described in Example 1 are shown, for phosphate type C crystals, the results of the crystals obtained by the (f) method described in Example 3 are shown, and for maleic acid type F crystals, the results of maleic acid type F crystals obtained by the method described in Experimental Example 4 are shown.

[0170] In the comparative test results shown below, the results of the malonic acid H-type crystal obtained by the method described in Experimental Example 4 are shown. In addition to the H-type, malonic acid can also obtain G-type and I-type crystals, which contain toluene in the molecule. Toluene is a compound known to cause obstacles to the central nervous system, etc., and it is not ideal to include it in a pharmaceutical raw material from the perspective of safety. It is known that the G-type and I-type crystals are not suitable as crystals for pharmaceutical raw materials, so they were not subjected to comparative tests.

[0171] The thermal stability, hygroscopicity and deliquescent property, and chemical stability of each of the above-mentioned crystals were evaluated.

[0172] <Thermal Stability Evaluation>

[0173] The evaluation was performed under the following conditions using a thermogravimetric / differential thermal simultaneous measurement apparatus TG / DTA7200 (SII NanoTechnology Co., Ltd.).

[0174] Heating speed: 10K / min

[0175] Atmosphere: Nitrogen 200mL / min

[0176] <Evaluation of Hygroscopicity and Deliquescent Properties>

[0177] The moisture adsorption measuring device DVS-1 or DVS-intrinsic (Surface Measurement Systems Limited) is used for evaluation in the following manner. The sample is placed in a dish that has been calibrated for tare weight in advance, and the weight at the start of the measurement is precisely measured by hanging it on the precision balance of the device. The weight change when the humidity is changed step by step is recorded over time, and the equilibrium weight at each humidity is calculated. The weight change rate at each humidity is calculated using the dry state (0% RH) or the anhydrous substance converted from the moisture content at the start confirmed by other methods as a reference.

[0178] <Chemical Stability Evaluation>

[0179] The sample was sealed at 60°C and stored at 60°C and 75% RH for one week. The increase or decrease of the relevant substance before and after storage was calculated based on the area percentage of each peak using high performance liquid chromatography, and the state after storage was observed.

[0180] The results are shown in Table 7 below.

[0181] [Table 7]

[0182]

[0183] As a solid with reproducibility in pyrrolidine compound A and a mixture containing it, it is found that hydrochloride amorphous, free body amorphous, free body crystal, phosphoric acid A type + B type crystal, phosphoric acid B type crystal as a mode of the crystal of the present invention, phosphoric acid C type crystal, maleic acid F type crystal, malonic acid G type crystal, malonic acid H type crystal, and malonic acid I type crystal. Among these, for free body crystal, it is impossible to make the residual solvent below the reference value specified by ICH, and for malonic acid G type crystal and malonic acid I type crystal, toluene is contained in the molecule, and it is not suitable as a crystal of the original medicine of pharmaceutical products from the viewpoint of safety. Maleic acid F type crystal also cannot completely remove toluene as a residual solvent. On the other hand, residual solvent is not confirmed from the crystal of the present invention, and toluene is not contained in the molecule, therefore, from the viewpoint of safety, it is considered to be a crystal without problems.

[0184] In addition, deliquescent properties were observed in amorphous hydrochloride, phosphoric acid type C crystals, maleic acid type F crystals, and malonic acid type H crystals, but deliquescent properties were not observed in phosphoric acid type B crystals. The weight change at 90% RH was less than 1%, and even when stored at 60°C and 75% RH for one week, the increase in related substances was only 0.05%, indicating that the crystals were stable to humidity and chemically very stable.

[0185] Furthermore, when the free amorphous body and the phosphate type A + B crystals were heated to 130°C, a weight change of more than 2% was observed, but the phosphate type B crystals showed no weight change even at above 200°C, indicating that they were crystals with excellent thermal stability.

[0186] Experimental Example 7 Study on the Precipitation Conditions of the Crystals of the Present Invention

[0187] [Chemical formula 5]

[0188]

[0189] Condition 1

[0190] Compounds 5 To a solution of ethyl acetate (67.75 g) (15.00 g), potassium carbonate aqueous solution (2.64 g potassium carbonate, 75 mL purified water) was added dropwise at 25°C, and stirred at 300 rpm for 30 minutes. The organic layer was separated, washed with purified water, and then concentrated under reduced pressure. Ethanol (59.03 g) was added, and the volume was concentrated under reduced pressure to 27 mL. This operation was repeated twice.

[0191] To the obtained concentrated mixture, ethanol (24.32 g) was added until the volume became 45 mL, and 24% sodium hydroxide aqueous solution (4.79 g) and purified water (12 mL) were added dropwise at 25°C, and stirred at 300 rpm for 6 hours. To the reaction mixture, 85% phosphoric acid aqueous solution (6.61 g) and purified water (22.5 mL, relative to the compound) were added dropwise over 5 minutes. 4 Then, purified water (90 mL, relative to the compound) was added dropwise over 30 minutes. 4 After the addition of purified water was completed, the mixture was stirred for 30 minutes, the reaction temperature was adjusted to 35°C, and seed crystals (0.3746 g, relative to the compound) were added. 4 The weight ratio was 0.025 times the weight of the mixture). After 10 hours from the addition of the seed crystal, the reaction temperature was set to 20°C and the mixture was stirred for 30 minutes. The insoluble matter was filtered and dried under reduced pressure to obtain the present invention crystal (7.48 g).

[0192] The obtained crystals had poor filterability and took a long time to filter. Furthermore, the wet product before drying was in a slurry state and had poor handleability.

[0193] When the particle size of the obtained crystal was measured, the mode particle size was about 6 μm. The particle size distribution of the crystal obtained under condition 1 was measured ( Figure 5-1 ).

[0194] Condition 2

[0195] Compounds3 To a solution of 17.58 g of ethanol (53.20 g) was added an aqueous sodium hydroxide solution (24%, 4.67 g) and purified water (16.20 g), and the mixture was stirred at 40°C for 3 hours to obtain the compound 4 To 18.28 g of the obtained compound 4 Phosphoric acid (1.91 g, 2.6 equivalents) and purified water (7.49 g, relative to compound ) were added to the solution at 35 °C. 4 After stirring for 1 hour, seed crystals (125 mg, relative to the compound 4 17 hours and 30 minutes after the addition of the seed crystals, purified water (30.0 mL, relative to the weight of the compound) was added over 2 hours. 4 After 10 hours, the reaction temperature was set to 20°C and stirring was continued. After 27 hours, the solid was filtered out and purified water (25.23 g, relative to the compound) was used. 4 The solid was washed with 5 times the weight of the solid by volume. The solid was dried at 50° C. to obtain the present invention crystal (4.01 g).

[0196] Sampling was performed 16 hours and 21 hours after the addition of the seed crystals, and the precipitation rates of crystals were calculated by HPLC to find that they were 4% and 97%, respectively.

[0197] It is known that when the amount of purified water before seeding is small as in condition 2, the crystal precipitation rate becomes extremely low. That is, it is known that in order to precipitate the crystal of the present invention, the amount of purified water added in the ethanol solution, i.e., the composition of the crystallization solvent is important. In addition, when purified water is further added to the solution with a low precipitation rate, although crystals are precipitated, similarly to condition 1, crystals with poor operability such as filtration are obtained.

[0198] Condition 3

[0199] Compounds 3 To a solution of 1,2-dihydro-1-nitropropene (26.37 g) in ethanol (79.82 g) was added an aqueous sodium hydroxide solution (24%, 7.01 g) and purified water (24.30 g), and the mixture was stirred at 40°C for 4 hours and 30 minutes to obtain the compound 4 To the obtained compound 4 Phosphoric acid (9.70 g, 2.2 equivalents) and purified water (45.00 g, relative to compound ) were added to the solution at 20 °C. 4 The weight of the compound was 1.5 times the volume ratio), and purified water (45.13 g, relative to the compound 4After stirring at 30°C for 40 minutes, seed crystals (751 mg, relative to the compound 4 16 hours later, purified water (135 mL, relative to the weight of the compound) was added over 2 hours. 4 The solid was filtered out and washed with purified water (150.02 g, relative to the compound) and the volume ratio was 4.5 times). After 6 hours, the temperature was adjusted to 20°C and stirred for another hour. 4 The solid was washed with 5 times the weight of the solid by volume. The solid was dried at 50° C. to obtain the present invention crystal (26.95 g).

[0200] When the particle size of the obtained crystals was measured, the mode particle size was about 10 μm. The operability of filtering and the like of the obtained crystals was good. The particle size distribution of the crystals obtained under condition 3 was measured ( Figure 5-2 ).

[0201] As described above, the temperature is set to about 30°C, purified water in an amount as described in condition 3 is added, seed crystals are added, and after leaving for a certain period of time to allow crystals to grow significantly, purified water is further added, thereby obtaining crystals with good precipitation rate and operability.

[0202] [Table 8]

[0203] Table 8

[0204] Relationship between the amount of purified water added, seeding temperature and precipitation rate under experimental conditions 2 and 3

[0205]

[0206] Reaction apparatus and stirring conditions

[0207] Condition 2

[0208] Reaction device: EasyMax (registered trademark) (Mettler-Toledo)

[0209] Stirring conditions: 300rpm

[0210] Condition 3

[0211] Reaction apparatus: OptyMax (registered trademark) (Mettler-Toledo)

[0212] Stirring conditions: 250rpm

[0213] HPLC assay conditions

[0214] Device Name:

[0215] Column: GL Science, Inertsil ODS-3V (5μm, 4.6X150mm)

[0216] Mobile layer A: water / acetonitrile / trifluoroacetic acid = 1900:100:1

[0217] Mobile layer B: water / acetonitrile / trifluoroacetic acid = 100:1900:1

[0218] Particle trend determination conditions

[0219] Equipment name: Particle Track (registered trademark) MALVERN, Mastersizer 2000 (wet type)

[0220] Measuring range: 0.020~2000.000μm

[0221] Measurement time: 10 seconds

[0222] Measuring intensity range: 3.0~20.0%

[0223] Stirring speed: about 2000rpm

[0224] As described above, as in condition 3, after adding sufficient purified water, seed crystals are added, and after leaving for a certain period of time to allow the crystals to grow significantly, purified water is further added, thereby ensuring a sufficient precipitation amount and obtaining crystals containing a large amount of crystals with good fluidity and filterability and a large chord length. As a result, the operability of filtration, etc. is improved.

[0225] Experimental Example 8 Human MC1R agonist assay

[0226] Using the crystal of the present invention, the intracellular cAMP concentration was measured according to the following method described in Experimental Example 1 of Patent Document 1, and EC 50 value.

[0227] (1) Cell culture method

[0228] The human melanoma cell line HBL was used for the assay of human MC1R agonist activity. HBL was cultured using F-10 nutrient mixture containing 10% FCS and penicillin-streptomycin.

[0229] (2) cAMP detection and data calculation

[0230] The compound solution of each concentration was mixed with cAMP detection buffer (HBSS (Hank's Balanced Salt Solution) containing 10 mM HEPES and 0.1% BSA) and dispensed into a 96-well plate. HBL was used to make 5×10 4 The cells were suspended in a cAMP detection buffer containing 0.5 mM IBMX at 400 μg / mL, dispensed into the above-mentioned 96-well plate, mixed, and allowed to stand at 37°C for 30 minutes. The intracellular cAMP concentration was measured by Envision's fluorescence method (ex. 320 nm, em. 590 nm, and 665 nm). The obtained data were calculated using Prism 5.02 based on the ratio (665 nm measurement value / 590 nm measurement value × 10000) to determine the quantitative value of the cAMP concentration, and the induction % value was calculated (the average cAMP concentration of the background medium (vehicle) was set to 0%, and the αMSH concentration was set to 10 -6 EC was calculated by taking the average cAMP concentration of each sample at 100% 50 value.

[0231] As a result, the crystal of the present invention showed an EC of 5.3 nM. 50 The value is 0.04, which is a crystal with strong human MC1R agonist activity.

[0232] Industrial Applicability

[0233] The crystals of the present invention do not leave any solvent used when obtaining the crystals, have excellent thermal stability, have little weight change with respect to humidity, are stable, do not deliquesce, have excellent chemical stability, and from the perspective of safety, do not contain any compound that may have an adverse effect on a living body. Furthermore, the crystals can be obtained with good reproducibility using an industrially suitable method, and are therefore excellent crystals as pharmaceutical raw materials.

Claims

1. A crystal comprising equimolar amounts of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid and phosphoric acid, and which is a co-crystal of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid and phosphoric acid, in, In the powder X-ray diffraction spectrum, peaks were shown at diffraction angles represented by 2θ of 5.7°±0.2°, 11.5°±0.2°, 13.9°±0.2°, 19.0°±0.2°, and 21.9°±0.2°.

2. The crystal according to claim 1, wherein In differential scanning calorimetry analysis, it has an endothermic peak at 230°C to 240°C.

3. The crystal according to claim 1 or 2, which is obtained by adding seed crystals to a mixture of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid, phosphoric acid and a good solvent.

4. The crystal according to claim 1 or 2, which is obtained by adding a poor solvent to a mixture of 1-{2-[(3S,4R)-1-[(3R,4R)-1-cyclopentyl-3-fluoro-4-(4-methoxyphenyl)pyrrolidine-3-carbonyl]-4-(methoxymethyl)pyrrolidin-3-yl]-5-(trifluoromethyl)phenyl}piperidine-4-carboxylic acid, phosphoric acid and a good solvent, adding a seed crystal, and then further adding a poor solvent. 5 . A melanocortin receptor 1 agonist comprising the crystal according to claim 1 as an active ingredient.

6. A pharmaceutical composition comprising the crystal according to any one of claims 1 to 4 and a pharmaceutically acceptable additive. 7 . The pharmaceutical composition according to claim 6 , which is used for preventing or treating a disease whose symptoms are expected to be improved by activating melanocortin receptor 1.

8. The pharmaceutical composition according to claim 7, wherein The disease is one or more diseases selected from osteoarthritis, inflammatory bowel disease, systemic scleroderma, psoriasis, fibrosis, protoporphyria, systemic lupus erythematosus, skin cancer, vitiligo, alopecia, pain, ischemia / reperfusion injury, inflammatory diseases of the brain, hepatitis, sepsis / septic shock, nephritis, transplantation, exacerbation of HIV disease, vasculitis, uveitis, retinitis pigmentosa, age-related macular degeneration, microbial infection, celiac disease and nephrotic syndrome.

9. The pharmaceutical composition according to claim 7, wherein The disease is one or more diseases selected from the group consisting of rheumatoid arthritis, gouty arthritis, melanoma, and melanoma infiltration. 10 . Use of the crystal according to claim 1 for producing a medicament for preventing or treating a disease whose symptoms are expected to be improved by activation of melanocortin receptor 1.

11. The crystal according to claim 1 or 2, which is used for preventing or treating a disease whose symptoms are expected to be improved by activation of melanocortin receptor 1.

Citation Information

Patent Citations

  • Novel pyrrolidine compound and application as melanocortin receptor agonist

    WO2015182723A1

  • Novel pyrrolidine compound and application as melanocortin receptor agonist

    CN106458887A

  • Pharmaceutical composition

    JP2017105765A